2,5-PRODAN Derivatives as Highly Sensitive Sensors of Low Solvent Acidity - Yoon, Alexandra H. (Molecules, 2014)
Two 5-acyl-2-dimethylaminonaphthalene derivatives, one with a propionyl group and the other with a fused cyclohexanone ring, are investigated as sensors of H-bond-donating ability in protic solvents of low solvent acidity. Their fluorescence is highly quenched in protic solvents, and the quenching order of magnitude is linearly related to the H-bond-donating ability of the solvent as quantified by the solvent acidity (SA) scale. As the solvent acidity increases from 0.15 to 0.40, the fluorescence for both is quenched by more than a factor of ten; thus, they are extremely sensitive sensors of the hydrogen-bond-donating ability in this weakly acidic range. Preferential solvation studies suggest that quenching occurs from a doubly H-bonded excited state.